2015
DOI: 10.1016/j.physd.2015.09.010
|View full text |Cite
|
Sign up to set email alerts
|

The effects of wind and nonlinear damping on rogue waves and permanent downshift

Abstract: openAccessArticle: Falsecover date: 2015-12-01pii: S0167-2789(15)00177-3Harvest Date: 2016-01-06 13:08:11issueName:Page Range: 81-81href scidir: http://www.sciencedirect.com/science/article/pii/S0167278915001773pubType

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…We report here briefly the evolution of the most important quantities (norm, momentum, spectral mean) in the damped-forced model, in order to better compare to the approximated results reported in the text, Eqs. (6c) and (7). From Eq.…”
Section: Appendix B: Evolution Of Momentsmentioning
confidence: 99%
See 1 more Smart Citation
“…We report here briefly the evolution of the most important quantities (norm, momentum, spectral mean) in the damped-forced model, in order to better compare to the approximated results reported in the text, Eqs. (6c) and (7). From Eq.…”
Section: Appendix B: Evolution Of Momentsmentioning
confidence: 99%
“…Naturally, the first step is to include in one dimensional propagation equations the two main forcing and damping mechanisms, viscosity and wind. The former is an unavoidable limit in laboratory facilities, the impact of which on propagation is non-trivial [4][5][6][7][8][9]; the latter [10,11] has attracted much interest in theoretical and experimental efforts, particularly in recent years [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the spectral downshift observed in BFI [15] can be often explained in the HONLS framework. However, in the last decades much effort has been devoted to discuss the properties of this model and to include other effects, such as viscosity or wind [16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Even so, frequency downshifting is not captured by either the linear damped NLS or Dysthe equations since momentum and energy decay at the same rate, thus preserving the spectral center. However, the nonlinear damped higher order NLS (Equation ( 1)) exhibits permanent downshifting [23]) and, in a comparative study, it was shown to be one of the most accurate models for predicting the downshifting observed in a set of laboratory experiments [7].…”
Section: Introductionmentioning
confidence: 99%